2014
DOI: 10.1002/stem.1722
|View full text |Cite
|
Sign up to set email alerts
|

Concise Review: Androgen Receptor Differential Roles in Stem/Progenitor Cells Including Prostate, Embryonic, Stromal, and Hematopoietic Lineages

Abstract: Stem/progenitor (S/P) cells are special types of cells that have the ability to generate tissues throughout their entire lifetime and play key roles in the developmental process. Androgen and the androgen receptor (AR) signals are the critical determinants in male gender development, suggesting that androgen and AR signals might modulate the behavior of S/P cells. In this review, we summarize the AR effects on the behavior of S/P cells, including self-renewal, proliferation, apoptosis, and differentiation in n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
40
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(45 citation statements)
references
References 103 publications
(144 reference statements)
4
40
0
1
Order By: Relevance
“…Surprisingly, knockdown of SOCS3 also reduced the induction of the stemness genes. This paradoxical effect could be explained by the increased androgen receptor activity upon knockdown of SOCS3, which is known to induce differentiation and suppress self-renewal (19). On the basis of these findings, we speculate that patients with SOCS3 promoter hypermethylation undergoing anti-androgen therapy could benefit from combinatorial treatment with DNA methyltransferase inhibitors, such as azacitidine and decitabine, clinically approved drugs for treatment of myelodysplastic syndromes and acute myeloid leukemia (49).…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…Surprisingly, knockdown of SOCS3 also reduced the induction of the stemness genes. This paradoxical effect could be explained by the increased androgen receptor activity upon knockdown of SOCS3, which is known to induce differentiation and suppress self-renewal (19). On the basis of these findings, we speculate that patients with SOCS3 promoter hypermethylation undergoing anti-androgen therapy could benefit from combinatorial treatment with DNA methyltransferase inhibitors, such as azacitidine and decitabine, clinically approved drugs for treatment of myelodysplastic syndromes and acute myeloid leukemia (49).…”
Section: Discussionmentioning
confidence: 87%
“…Thus, the IL6/JAK/STAT3 and AR signaling pathways, which are investigated in this study, are linked to prostate cancer progression and the development of castration resistance. In addition, several groups have demonstrated that activation of the IL6/JAK/STAT3 pathway is required for maintenance of stem cell properties in human malignancies (5,(16)(17)(18), whereas androgen receptor activity is known to induce differentiation and suppress self-renewal and proliferation of prostate cancer cells (19).…”
Section: Introductionmentioning
confidence: 99%
“…The role of ERα signaling in breast cancer initiating cells is an area of active investigation 39,40 , and so is that of AR in prostate cancer 41,42 . By contrast, the role that these pathways play in self-renewal of initiating cancer cells of other types is a mostly unexplored topic and important area of future investigation.…”
Section: Introduction (Epidemiology)mentioning
confidence: 99%
“…These effects may be reduced or counter-balanced by increasing erythropoietin (EPO) levels (43) and one acknowledged mechanism involved in the hematological effects of androgens is the promotion of erythroid progenitor expansion by increasing EPO levels (44). Furthermore, androgen and androgen receptor signals may promote the proliferation of HSCs/HPCs and stimulate hematopoietic lineage differentiation (45). Another potential mechanism may be that the addition of testosterone may enhance the G1-S transition rate in the cell cycle and the survival of HSCs (32).…”
Section: Discussionmentioning
confidence: 99%
“…The control groups were treated without hormones and at the same oxygen concentration as other groups. The concentrations of these hormones were determined as previously described (18)(19)(20)(21)(22)(23). Cells were incubated in an atmosphere containing 20% O 2 (normoxic conditions) using a Heal Force Tris-gas incubator (HF240; Heal Force Bio-meditech Holdings Limited, Shanghai, China) or 1% O 2 (hypoxic conditions; HF100; Heal Force Bio-meditech Holdings Limited) containing 5% CO 2 at 37˚C.…”
Section: Hormone Screening Test Cd34mentioning
confidence: 99%